Adherence to a priori-Defined Diet Quality Indices Throughout the Early Disease Course Is Associated With Survival in Head and Neck Cancer Survivors: An Application Involving Marginal Structural Models - Maino Vieytes, Christian A.; Rodriguez-Zas, Sandra L.; Madak-Erdogan, Zeynep; Smith, Rebecca L.; Zarins, Katie R.; Wolf, Gregory T.; Rozek, Laura S.; Mondul, Alison M.; Arthur, Anna E. (Frontiers in Nutrition, 2022)
No studies, to date, have scrutinized the role of a priori dietary patterns on prognosis following a head and neck squamous cell carcinoma (HNSCC) diagnosis. The purpose of this analysis was to evaluate associations between adherence to six a priori defined diet quality indices (including AHEI-2010, aMED, DASH, and three low-carbohydrate indices) throughout the first three years of observation and all-cause and cancer-specific mortalities in 468 newly diagnosed HNSCC patients from the University of Michigan Head and Neck Specialized Program of Research Excellence (UM-SPORE). Dietary intake data were measured using a food frequency questionnaire administered at three annual time points commencing at study entry. Deaths and their causes were documented throughout the study using various data sources. Marginal structural Cox proportional hazards models were used to evaluate the role of diet quality, as a time-varying covariate, on mortality. There were 93 deaths from all causes and 74 cancer-related deaths adjudicated throughout the observation period. There was a strong inverse association between adherence to the AHEI-2010, all-cause mortality (HRQ5-Q1: 0.07, 95% CI: 0.01-0.43, p¬trend: 0.04), and cancer-specific mortality (HRQ5-Q1: 0.15, 95% CI: 0.02-1.07, p¬trend: 0.04). Other more modest associations were noted for the low-carbohydrate indices. In sum, higher adherence to the AHEI-2010 and a plant-based low-carbohydrate index throughout the first three years since diagnosis may bolster survival and prognosis in newly diagnosed HNSCC patients.